Cochrane Database of Systematic Reviews 1999
DOI: 10.1002/14651858.cd001421
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing blood loss during the treatment of cervical intraepithelial neoplasia

Abstract: Background-Cervical intraepithelial neoplasia (CIN) is the most common pre-malignant lesion. Surgical treatments for CIN are commonly associated with blood loss. Objectives-To assess the effectiveness and safety of interventions for preventing blood loss during the treatment of CIN. Search methods-We searched the Cochrane Gynaecological Cancer Group Trials Register, MEDLINE, EMBASE and CENTRAL up to April 2009. We also searched registers of clinical trials, abstracts of scientific meetings and reference lists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
0
13
0
2
Order By: Relevance
“…Compiled retrospective data have demonstrated that LEEP with negative SMs is equally safe and effective in managing patients with AIS who desire to preserve their fertility [ 6 , 13 , 14 ]. In addition, LEEP is technically easier and less expensive and is associated with less morbidity, such as pain, cervical stenosis, and hemorrhage, than CKC [ 7 , 8 ]. More importantly, LEEP has clinical advantages over CKC in terms of future pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compiled retrospective data have demonstrated that LEEP with negative SMs is equally safe and effective in managing patients with AIS who desire to preserve their fertility [ 6 , 13 , 14 ]. In addition, LEEP is technically easier and less expensive and is associated with less morbidity, such as pain, cervical stenosis, and hemorrhage, than CKC [ 7 , 8 ]. More importantly, LEEP has clinical advantages over CKC in terms of future pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Conization, especially CKC biopsy, has been used for the diagnosis and treatment of cervical intraepithelial neoplasia (CIN), including carcinoma in situ. However, the recently introduced LEEP has become more common due to its technical ease and lower morbidity [ 7 , 8 ]. In addition, LEEP is usually performed under regional anesthesia in an outpatient clinic with significantly lower costs.…”
Section: Introductionmentioning
confidence: 99%
“…Obstetric and gynecologic hemorrhage can also lead to severe morbidity and postpartum hemorrhage remains a leading cause of maternal death ( American College of Obstetricians and Gynecologists, 2006 ). Cervical and vaginal lacerations in particular can cause large volume blood loss and traditional management includes hemostatic suturing and vaginal gauze packing ( Ghirardini et al, 2012 , Martin-Hirsch et al, 2010 ). Occasionally, cervical and vaginal hemorrhage may be difficult to control with conventional interventions due to friable tissue, multiple mucosal lacerations or coagulopathies ( Patel et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly used for the prevention of excessive bleeding. 121,182,[187][188][189][190][191] Treatment of HAE patients with TA reduces the frequency of swelling in 70% of the patients. 156,157 Because of the virilizing effects of androgens, TA can be used as the first agent of choice in children with HAE.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%